(untitled) (Journal of Laboratory Animal Science, 2022)
Health monitoring surveillance is an essential requirement of barrier facility as animal research is largely depends on health status of laboratory animals being used. Early identification of pathogens by using ideal methods can prevent infections; otherwise confounding variables can occur in the experimental results of biomedical research. Syngene has been importing animals from at least 12 different barriers facilities from USA/Europe/India to conduct planned experiments at appropriate ages. However, the limiting factor was stringent quarantine period (upto 21 days), which further increases age of the animals. In order to maintain the healthy animals, comprehensive testing strategies have been implemented in a programmed manner to identify infectious agents during early stages, thereby preventing the spread of contamination to other areas within the vivarium. The primary aim was to screen representative samples of each batch as per the schedule apart from established sentinel program which were further analyzed at 6, 12 and 18 weeks interval including comprehensive annual testing. Based on the inherent challenges, a diagnostic laboratory was established at site to screen pathogens using validated methods primarily by ELISA, IFA to detect antibodies and PCR for nucleic acid detection as well as rapid screening which has been a prerequisite for early quarantine release of animals for experiments. Alternatively, MFIA has been used as high throughput assay for rodent pathogens at periodical intervals along with other methods. In addition, bacterial pathogens if any can be identified by using VITEK apart from the routine contact plating of swab samples taken from animals. The in-house diagnostic laboratory including at least 4 outside laboratories have been employed for weekly and/or sentinel samples screening by serological assays such as ELISA, MFIA, IFA and molecular technique of PCR for rodent pathogens. Collectively, the robust screening systems at multi-site laboratories which eventually reduced turnaround time by adopting high throughput assay including confirmatory methods to obtain consistent and reliable results of rodent pathogens.